Can crowdsourced data help to optimize atopic dermatitis treatment? Comparing web search data and environmental data in Germany. (31st December 2021) - Mick, A.; Tizek, L.; Schielein, M.; Zink, A.
Abstract: Background: Atopic dermatitis (AD) is one of the most common chronic skin diseases worldwide, showing various manifestations and having a severe impact on quality of life. As previous studies demonstrated, internet search analysis can help identify public interest in diseases and possible influencing factors on search behavior. Objective: To identify AD‐related topics of interest in Germany using internet search volume. Methods: Google Ads Keyword Planner was used to identify AD‐related search terms including their search volume in Germany on a national level as well as in 16 selected cities from January 2016 to December 2019. Identified keywords were qualitatively analyzed, and temporal trends as well as the influence of seasonal and environmental factors on search volume were assessed. Results: Overall, 1222 AD‐related search terms with a search volume of 8 842 360 searches were identified. An increase from 2016 to 2019 and seasonal peaks from January to April of each year were observed. Nationwide, the search volume correlated with mean monthly temperature and sun duration. With increasing temperature and sun duration, a significant decrease in search queries was observed. The most populated cities showed the lowest number of searches per 100 000 inhabitants (Berlin, Hamburg, and Munich). In the eight categories formed (comorbidities, general, influential factors, localization, stage of life, symptoms/severity, therapy/information, and questions on AD), the highest proportion of search queries were assigned to the category "therapy/information" in most cities. In this category, a focus on the topics of "alternative medicine" and "home remedies" could be observed. Conclusion: The overall high and increasing search volume indicates a high interest in AD‐related topics, especially regarding treatment and disease education. Information provided by internet search volume analyses can optimize AD therapy and patient‐centered care by providing insight into patient needs and predicting potential climatic trigger factors.